The present situation and development of standardized training for the Traditional Chinese Medicine nursing staff with low seniority (低年资中医护理人员规范化培训现状与发展) - LI Qian (李倩); ZHOU Gexia (周革霞); LIU Xiaoyu (刘潇禹) (中西医结合护理, 2022)
This paper reviewed the studies on standardized training of the Traditional Chinese Medicine (TCM) nursing staff with low seniority from perspectives of the present situation, potential problems, training modes, assessment methods and future development, in order to provide reference for relevant research and the training of TCM nursing staff with low seniority. (本文从低年资中医护理人员规范化培训现状、面临的问题、培训模式、考核方式及未来的发展方向等方面进行综述, 以期为相关研究及临床低年资中医护理人员的培训提供参考。)